2010
DOI: 10.1073/pnas.1006284107
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the N terminus of cadherin 23 reveals a new adhesion mechanism for a subset of cadherin superfamily members

Abstract: The cadherin superfamily encodes more than 100 receptors with diverse functions in tissue development and homeostasis. Classical cadherins mediate adhesion by binding interactions that depend on their N-terminal extracellular cadherin (EC) domains, which swap Nterminal β-strands. Sequence alignments suggest that the strandswap binding mode is not commonly used by functionally divergent cadherins. Here, we have determined the structure of the EC1-EC2 domains of cadherin 23 (CDH23), which binds to protocadherin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…7). Each upper tip link is expected to have very limited amounts of cadherin23 homodimers, considering that the diameter of each tip link is about 8 -10 nm (4), and that the first and second cadherin repeats of cadherin23 are about 2.5 nm in width (6,38). We also assume here that cadherin23 in hair cell stereoclilia contains exon68 (18 -22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Each upper tip link is expected to have very limited amounts of cadherin23 homodimers, considering that the diameter of each tip link is about 8 -10 nm (4), and that the first and second cadherin repeats of cadherin23 are about 2.5 nm in width (6,38). We also assume here that cadherin23 in hair cell stereoclilia contains exon68 (18 -22).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanoelectrical transduction channel is present at the tips of all but the tallest stereocilia (1), and gated by a filamentous ultrastructure, called tip link, to control stereocilia depolarization and electric signal propagation (2,3). Tip link connects the tip of one stereocilium to the side of the nearby taller stereocilium (4), and is formed by cadherin23 homodimer in trans association with protocadherin15 homodimer (5)(6)(7)(8). Both cadherin23 and protocadherin15 are usher syndrome I, single-transmembrane adhesion proteins with a long extracellular cadherin repeats followed by a short cytoplasmic tail.…”
mentioning
confidence: 99%
“…The mechanism for the heterophilic interaction between Cdh23 and Pcdh15 is somewhat different from the strandswap binding of classical cadherins (84). The NH 2 terminus of Cdh23 contains polar amino acids that bind Ca 2ϩ , and this Ca 2ϩ binding is critical for the interaction of Cdh23 with Pcdh15.…”
Section: B Cadherin 23 and Protocadherin 15 In Inner Ear Functionsmentioning
confidence: 98%
“…Molecular dynamics simulations and binding experiments have indicated that the bond formed by protocadherin-15 and cadherin-23 is mechanically strong enough to withstand the forces applied to the tip-link during hair bundle deflection (Sotomayor et al 2012). The three-dimensional (3D) structures of the cadherin-23 and protocadherin-15 EC1 domains are similar to those of other cadherins (three Ca 2þ -binding sites (1, 2, and 3) at the linker between EC1 and EC2), but with several unusual features, such as an elongated N-terminus stabilised at the tip by Ca 2þ -binding site 0 (Elledge et al 2010;Sotomayor et al 2010 , about 20-40 μM, in the endolymph (Bosher and Warren 1978).…”
Section: Two Cadherin-related Proteins Form the Tip-link A Key Compomentioning
confidence: 92%